2013
DOI: 10.4037/ajcc2013565
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Nurses and Physicians of Their Communication at Night About Intensive Care Patients' Pain, Agitation, and Delirium

Abstract: Background Ineffective daytime nurse-physician communication in intensive care adversely affects patients' outcomes. Nurses' and physicians' communications and perceptions of this communication at night are unknown. Objectives To determine perceptions of nurses and physicians of their communication with each other at night in the intensive care unit about patients' pain, agitation, and delirium and to develop a qualitative survey instrument to investigate this topic. Methods A validated survey was distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Patients' perceptions of self in the ICU were related to physical signs and symptoms, such as enduring physical pain and discomfort, inability to maintain daily activities, feeling fatigued, lacking full consciousness, and considering themselves as an abnormal person while in the ICU [18]. Other studies showed that lack of privacy, fear, pain, and noise were the most frequently reported negative experiences by patients in ICUs [16], whereas the lack of communication, pain, and discomfort were found as the major sources of distress reported by mechanically ventilated patients in the ICU [19,20].…”
Section: Introductionmentioning
confidence: 98%
“…Patients' perceptions of self in the ICU were related to physical signs and symptoms, such as enduring physical pain and discomfort, inability to maintain daily activities, feeling fatigued, lacking full consciousness, and considering themselves as an abnormal person while in the ICU [18]. Other studies showed that lack of privacy, fear, pain, and noise were the most frequently reported negative experiences by patients in ICUs [16], whereas the lack of communication, pain, and discomfort were found as the major sources of distress reported by mechanically ventilated patients in the ICU [19,20].…”
Section: Introductionmentioning
confidence: 98%
“…Further discussion of these key factors that influence students' experiences which includes; support and confidence from faculty and clinical preceptor attitudes towards students and learning process, course content, and patients' acuity in the unit showed by students comments and feedback through the emerging themes [8]. Furthermore, sstrategies such as self-directed learning and preceptorship management were found to positively improve student's experiences.…”
Section: Discussionmentioning
confidence: 99%
“…More advantages of clinical experiences providing opportunities to interact with nurses and physicians in critical care and gain an understanding of the importance of interpersonal relationships as part of the nurse's role [3,8]. However, Tait et al, [15] support the view that there is a need for critical care placements to enhance this interactions and improving interpersonal skills.…”
Section: Journal Of Intensive and Critical Care Issn 2471-8505mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common information needs for physicians and nurses in clinical work are the patient’s diagnosis, drugs, and treatment, and the most common way to source out such information is through asking their colleagues [8]. The differences in the tasks handled lead to differences in information understood by physicians and nurses, and there are discrepancies in the assessments of patient conditions such as their rehabilitation and feelings [9]. During situations such as performing rounds and shift handovers, there are occurrences in which the information needs of physicians and nurses on patient conditions or follow-up status are overlooked [10].…”
Section: Introductionmentioning
confidence: 99%